PSYCHOSOMATICS AS A SCIENCE - Касымова Ф. С. (Web of Journals Publishing, 2024)
This article discusses the history of psychosomatics, the activities of scientists who have contributed to the development of this area of medicine.
Keywords: science, psychosomatics, psychoemotion, disease, biorhythm, somatic level, pathology, conflict, stress.